Analytical methods to access the chemical composition of an Euphorbia tirucalli anticancer latex from traditional Brazilian medicine. (12th June 2019) - de Souza, Larissa Silva; Puziol, Letícia C.; Tosta, Cristina Luz; Bittencourt, Milena L.F.; Ardisson, Juliana Santa; Kitagawa, Rodrigo Rezende; Filgueiras, Paulo Roberto; Kuster, Ricardo Machado
Abstract: Ethnopharmacological relevance: Euphorbia tirucalli L. is widely used by Brazilian folk medicine, mainly for its anticancer activity. However, its commercialization was banned by The Brazilian National Sanitary Surveillance Agency (ANVISA) due to the presence of some compounds considered toxic, such as the diterpene esters. Aim of the study: Chemical and biological analyses were performed with the Brazilian Euphorbia tirucalli latex to support its wide traditional use in Brazil. Material and methods: Latex was collected by using two procedures, in a solution of dichloromethane: methanol (3:1, 100 mL) and in 100 mL of distilled water. The first procedure was concentrated as a crude extract and the second one was partitioned with hexane and dichloromethane. The partitions and crude extract were subjected to phytochemical analyses using three different methods: Fourier transform-ion cyclotron resonance mass spectrometry (FT-ICR MS) with electrospray ionization sources in negative mode (ESI(−)) as well as in tandem mass spectrometry ESI(−) MS/MS and Atmospheric Pressure Chemical Ionization in positive mode (APCI(+)), Gas Chromatography coupled Mass Spectrometry (GC-MS) and Nuclear Magnetic Resonance (NMR) ( 1 H-NMR and 13 C-NMR). The cytotoxic potential was evaluated using the crude extract in macrophages RAW 264.7 and Gastric Adenocarcinoma (AGS) cancer cells. The evaluation of immunomodulatory activity was made through the detection of Nitric Oxide (NO) and cytokines as Tumor necrosis factor α (TNF-α) and Interleukin-6 (IL-6). Results: GC-MS showed the presence of some esters of fatty acids, for instance myristic, palmitic, stearic, oleic and linoleic acid and, mainly, triterpenes such as euphol and tirucallol. With NMR, most of the signals were related to triterpenoids euphol and tirucallol. However, when the latex was analyzed with ESI(−) FT-ICR MS, a wide variety of molecules from different classes of natural products (fatty acids, diterpenes, triterpenes, steroids) were found. On the other hand, when APCI(+)FT-ICR MS was used, the ion M +. At ratio mass-charge ( m/z ) 426.38567, related to triterpenes euphol and tirucallol masses, presented the most intense peak, with a mass error of −0.11, indicating high accuracy. Diterpene esters from 4-deoxyphorbol and ingenol were identified only by ESI(−)FT-ICR MS and ESI(−)FT-ICR MS/MS. When evaluated biologically, the crude latex showed immunomodulatory activity, as it reduced the production of the pro-inflammatory cytokines TNF-α, IL-6 and NO, and the effect on NO reduction was more significant, obtaining in a similar result to the N(ω)-Nitro-L-Arginine Methyl Ester (L-NAME) standards, as well as significant cytotoxic activity with half inhibitory concentration (IC50 ) values of 69.43 ± 1.29 μg/mL against AGS without damaging healthy ones. Conclusion: It was verified that the Brazilian Euphorbia tirucalli latex consists mainly of the triterpenes euphol and tirucallol, which may be the main cause of the anticancer activity attributed to the plant, but many other minor compounds could have been determined by the FT-ICR MS method, such as the diterpene esters. It has antitumor potential because it acts selectively against cancer cells and it also prevents the progression of tumors, because it carries an important immunomodulatory effect. Graphical abstract: Image 1